Dynamic Panel Data Analysis of the Human Development Index in Indonesia - Susilo, Joko Hadi; trifandha, siskha; Nkembo , Amon Frank; Astuti, Hartiningsih (Universitas Muhammadiyah Ponorogo, 2025)
The human Development Index is an important indicator for measuring people’s welfare. This study aims to determine the influence of household consumption, Gross Regional Domestic Product, investment, and government expenditure on the human development index (HDI) in 35 provinces in Indonesia for the period 2014-2023. Secondary data was sourced from the Central Statistics Agency and used to estimate the model, a dynamic panel approach was utilized, based on the Generalized Method of Moments. The results showed that Gross Regional Domestic Product (GRDP) has a significant influence on increasing the human development index (HDI), especially through increased consumption for education and health. In addition, achieving economic development in a country requires individual and collective human efforts in improving the quality of life. Important factors that must be built are the quality of human resources, facilities and infrastructure. Government spending focused on sectors that directly affect people's welfare can accelerate the improvement of the quality of human resources. This finding shows the importance of macroeconomic stability and fiscal policy effectiveness in supporting sustainable human development.